Modelos lineales generalizados para evaluar el efecto de las hormonas reguladoras auxinas y citoquininas en el crecimiento de gypsophilapaniculata l., 2010 - Bueno Villanueva, María Ysabel (2013)
The present research aims to apply the Generalized Linear Models a completely randomized factorial design on the experimental unit on 4 occasions to assess the effect of regulatory hormones auxin and cytokinin in the growth of L. Gypsophilapaniculata for multiplication in vitro. The sample consists of 55 glass jars containing the plant material with the appropriate nutrient medium, the research design is applied - experimental variables were considered : height , height of calluses , number of shoots , and number of leaves . Investigating treatments focused on MS medium (Murashige and Skoog, 1962) as control treatment. The methodology will be applied to the data that were collected in 2010 through an experiment conducted for empirical research in the area shelves in vitro culture in the Biotechnology Laboratory at the Academic Professional School of Agronomy of the UNT. From the results obtained it was concluded that generalized linear models suitable for evaluating the effect of regulatory hormones auxin and cytokinin on the growth of L. Gypsophilapaniculata for multiplication in vitro, giving a significant effect on the height , height and number of leaves calluses